Kanwal aathvin jamat k lia urdu ka guldasta - Ahsaan,Fouzia Farooqi (Karachi: Oxford university press, 2024)
The Oxford Kanwal Class 8 book is part of the educational series published by Oxford University Press for middle school students in Pakistan. It is designed to provide a well-rounded education that meets the national curriculum's standards for eighth-grade students. This book enhances students' proficiency in Urdu through literature that includes stories, poems, and essays. The texts often feature prominent writers and poets, introducing students to linguistic nuances, cultural themes, and moral values. Emphasis is placed on improving reading comprehension, grammar, and creative writing skills.
Keywords: Kanwal- textbook